2007
DOI: 10.14492/hokmj/1277472865
|View full text |Cite
|
Sign up to set email alerts
|

Two criteria of Wiener type for minimally thin sets and rarefied sets in a cylinder

Abstract: We shall give two criteria of Wiener type which characterize minimally thin sets and rarefied sets in a cylinder. We shall also show that a positive superharmonic function on a cylinder behaves regularly outside a rarefied set in a cylinder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There exists a measure τ on C n (Γ) such that supp τ ⊂ B j and τ (B j ) = 1. So we have for any W ∈ B jˆH which together with Theorem 1 in [9], gives that E is not rarefied at +∞ in H(Γ).…”
Section: Examplementioning
confidence: 73%
See 2 more Smart Citations
“…There exists a measure τ on C n (Γ) such that supp τ ⊂ B j and τ (B j ) = 1. So we have for any W ∈ B jˆH which together with Theorem 1 in [9], gives that E is not rarefied at +∞ in H(Γ).…”
Section: Examplementioning
confidence: 73%
“…On the other hand, the term "Green's function" has entered the vocabulary of probabilists in a way that may seem initially unrelated, namely as a measure the expected number of times that a discrete process visits a point, or the expected amount of time that a continuous process spends at a point. The reason that these two different notions have garnered the same name was discovered by Miyamoto and his collaborators in [10,9], who showed that in many cases in R n these two notions coincide, with L the Laplacian and the process in question Markov chains.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation